KAJI ULANG KONSEP HUBUNGAN ISLAM DAN DEMOKRASI - Nurdin, Ahmad Ali (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
This paper examines relationship between Islam and democracy. Agreements and disagreements among scholars about the concept are firstly discussed. It is followed by a discussion about formalist and substantive democracy. In examining relationship between Islam and democracy, the views of muslim scholars such as Sayyid Qutb, Al-Maududi, Ibnu Taimiyah and Al-Mawardi are examined. Finally, this paper describes Islamic values that compatible with democracy and examples of the views of muslim politicians in Southeast Asia particularly Indonesia and Malaysia about democracy and its implementation in these countries.